Combining the Curvature and Ligand Effects for Regioselective Growth on Au Nano-bipyramids - Jiang, Tingting; Zong, Jianpeng; Feng, Yuhua; Chen, Hongyu (Precision Chemistry, 2023)
We demonstrate the regioselective growth of Au on Au nano-bipyramids, either with etching of the tips, uniform coating except the tips, or forming a single island on the axial tip or an island on the equatorial corner. Importantly, the regioselectivity not only arises from the local curvature, as suggested by the recent literature, but also critically depends on the extent of ligand coverage on the seed surface. It is important to consider the competitive growth together with the curvature–ligand interplay: when there are insufficient ligands, they bind preferentially to the sharp tip for high surface energy, so that the remaining growth materials are diverted elsewhere; when the bipyramid is fully covered by ligands, the growth then selectively occurs at the tips because of the larger gaps among the ligands there. Our results demonstrate the great potentials in the rational design and synthesis when constructing sophisticated hybrid structures for functional nanomaterials.